Pengaruh kualitas layanan dan pengalaman wisata mengesankan terhadap kepuasan wisatawan pemandian alam Selokambang - Kabupaten Lumajang - Nuraeni, Afrilia Dewi; Astuti, Widji; Krisnanda, Rulli; Anggraini, Dhita Paramita (University of Merdeka Malang, 2024)
The importance of service and experience at tourism destinations in Indonesia can influence tourist satisfaction with that destination. The object of this research is the Selokambang Natural Baths, Lumajang Regency. The objectives of this research are 1. To describe the quality of the richness, impressive tourist experiences and tourist satisfaction of the Selokambang Natural Baths, Lumajang Regency. 2. Test and analyze the influence of service quality and impressive tourist experiences on tourist satisfaction at Selokambang Natural Baths, Lumajang Regency. 3. Test and analyze the quality of service and impressive tourist experiences that most influence tourist satisfaction at Selokambang Natural Baths, Lumajang Regency. The research used quantitative methods by distributing questionnaires and observing the Selokambang Natural Baths using the variables Service Quality, Impressive Tourist Experience and Tourist Satisfaction with a sample size of 100 respondents. From the analysis results obtained, this research shows that Service Quality and together have a positive effect on Tourist Satisfaction at Selokambang Natural Baths. Service Quality has a more positive influence than Impressive Tourist Experiences on Tourist Satisfaction.